Strategi Pemeliharaan Jalan dan Estimasi Perbaikan Berbasis Skor PCI - Subhan Mulyana; Sulwan Permana; Tendi Rismansyah (Jurnal Konstruksi, 2025)
The road is a vital infrastructure that plays an essential role in supporting community mobility and economic growth. Damage to roads caused by traffic loads, weather factors, or suboptimal construction quality can reduce pavement performance. The Ciawitali–Banjarwangi Road section in Garut Regency serves as one of the main access routes connecting three districts—Banjarwangi, Singajaya, and Pendeuy. This road has experienced significant deterioration, including alligator cracking, longitudinal cracking, potholes, raveling, and depressions. Such conditions require appropriate maintenance strategies and repair budgeting. This study employs the Pavement Condition Index (PCI) method based on ASTM D6433-18 standards to evaluate the level of road damage. A quantitative descriptive approach was used through a visual field survey covering a 3.72 km section divided into 48 segments. The damage data were analyzed to determine the PCI value of each segment, from which maintenance strategies were formulated according to the damage category, and repair cost estimates were calculated based on the Garut Regent Regulation No. 54 of 2024. The results show that PCI values vary across segments, with an average PCI of 40.29, indicating a Poor condition. However, the recommended maintenance strategies were determined based on the PCI category of each segment, resulting in different repair recommendations according to the type and severity of damage found. In general, an overlay is also recommended for all surveyed segments to restore the pavement to its original condition. The estimated total cost required for rehabilitating the Ciawitali–Banjarwangi Road section is IDR 3,960,228,074.67. These findings are expected to serve as an alternative reference for the local government in planning road maintenance and estimating budgets based on the actual damage data obtained.